68 Ga-complex lipophilicity and the targeting property of a urea-based PSMA inhibitor for PET imaging - Eder, Matthias; Mier, Walter; Haberkorn, Uwe (Bioconjugate chemistry, 2012)
Urea-based inhibitors of the prostate-specific membrane antigen (PSMA) represent low-molecular-weight pepidomimetics showing the ability to image PSMA-expressing prostate tumors. The highly efficient, acyclic Ga(III) chelator N,N′-bis [2-hydroxy-5-(carboxyethyl)benzyl] ethylenediamine-N,N′- diacetic acid (HBED-CC) was introduced as a lipophilic side chain into the hydrophilic pharmacophore Glu-NH-CO-NH-Lys which was found favorable to interact with the PSMA “active binding site”. This report describes the syntheses, in vitro binding analyses, and biodistribution data of the radiogallium labeled PSMA inhibitor Glu-NH-CO-NH-Lys(Ahx)-HBED-CC in comparison to the corresponding DOTA conjugate. The binding properties were analyzed using competitive cell binding and enzyme-based assays followed by internalization experiments. Compared to the DOTA-conjugate, the HBED-CC derivative showed reduced unspecific binding and considerable higher specific internalization in LNCaP cells. The 68Ga complex of the HBED-CC ligand exhibited higher specificity for PSMA expressing tumor cells resulting in improved in vivo properties. 68Ga labeled Glu-NH-CO-NH-Lys(Ahx)-HBED-CC showed fast blood and organ clearances, low liver accumulation, and high specific uptake in PSMA expressing organs and tumor. It could be demonstrated that the PET-imaging property of a urea-based PSMA inhibitor could significantly be improved with HBED-CC.
Im Titel ist die Zahl 68 hochgestellt
Gesehen am 05.06.2019